Persepsi Petani terhadap Ketersediaan Sarana dan Prasarana Usahatani di Subak Babakan Bengkel I Desa Getasan Kecamatan Petang Kabupaten Badung - I GEDE BAGUS ARYADHANA; NI WAYAN SRI ASTITI; I DEWA PUTU OKA SUARDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Perception Farmers Against Availability Infrastructures in Subak BabakanBengkel I Village Getasan Sub District Petang Badung. Agriculture in a broad sense includes smallholder agriculture, plantation, forestry,animal husbandry and fishery. Facilities and infrastructure are all things that are used asa tool in achieving the objectives of farmers in Subak Babakan Bengkel I VillageGetasan to support developments in running the farm. Based on this expected that thedevelopments in the availability of facilities and infrastructure in the farming. Based onthe above problems, the purpose of this study was to determine the perception offarmers on the availability of facilities and infrastructure of farming in Subak BabakanBengkel I Village Getasan Sub District Petang Badung. To prepare a good questionnairerequired some testing prior to conducting the study. Testing the questionnaire usingSPSS. The variable in this study is the perception of farmers on the availability offacilities and infrastructure of farming in Subak Babakan Bengkel I Village Getasan SubDistrict Petang Badung. Indicators of this study include the availability of means ofproduction, namely seeds, fertilizers, pesticides, plant growth regulator and inoculant.Alsintan (agricultural machinery), ie sprayer, power weeder, emposan tikus, reaper,tractors and power threaser. Network infrastructure includes farm roads, halls Subak,and irrigation canals. To maintain and increase the availability of facilities andinfrastructure in Subak Babakan Bengkel I of both categories should be excellentfarmers complementary facilities and infrastructure that can greatly help in a timeefficient and agricultural work in Subak